Halving poverty in South Africa: Growth and distributional aspects ; distributional implications of halving poverty in South Africa - Fiona Tregenna (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
The United Nations Millennium Declaration commits to halving extreme poverty between 2000 and 2015. The South African government has set a goal of halving poverty by 2014, although the meaning of this goal has not yet been defined. This article specifies government's stated target of halving poverty by 2014 in terms of specific measures of the poverty gap and poverty headcount ratio, using income and expenditure survey microdata. With the poverty line as defined here, approximately half the South African population falls below the poverty line. Despite this, the aggregate poverty gap is surprisingly small at about 3 per cent of GDP. Projections of the effects of distributional scenarios on poverty indicate that halving poverty appears feasible with moderate growth rates and fairly mild pro-poor distributional change.
Keywords: D30; D31; I32; 330; income distribution; poverty; inequality; South Africa; Armut; Einkommensverteilung; Armutspolitik; Millennium Development Goals; Südafrika